Praktik Akad Non Tunai dalam Pengelolaan Lahan Pertanian di Desa Dadapan Kabupaten Lomangan - Muhammad Farid; Ahmad Djalaluddin; Muhammad Haris Hidayatulloh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In Islam, it requires concrete evidence when a non-cash contract occurs. Such as using notes, witnesses, collateral or guarantor. This study aims to examine and analyze the practice of non-cash contracts carried out by the people of Dadapan village in muamalah farming. This research uses descriptive qualitative research because the research will be carried out or describe practices carried out in the community. The results of this study are that the practice is carried out between families, in this case the implementation of the contract is carried out orally. In the end, it had an impact on the payment of rent, which should have been made 2 times a year, to only once, namely during the low season.